Learners’ and teachers’ beliefs about learning tones and pinyin - Yang, Juan; Medwell, Jane (Springer, 2017)
This paper reports a study of the perceptions of English-speaking learners and teachers about the challenges and difficulties of Chinese as a Second Language (CSL) learning in England. The study involved a Likert-scale questionnaire and follow-up interviews with 37 university student learners, 443 school students and the 42 teachers of both groups. The questionnaires and interviews explored beliefs about language learning, about Chinese language learning and about language learning strategies. This paper focuses on the findings concerning the perceived challenges of speaking Chinese and of tones in learning Chinese. The findings of this study present a picture of teachers who are keen for their students to learn to speak and communicate in Chinese, and of students who are keen to take risks in speaking. However, in contrast to earlier findings about learners’ views about learning Chinese, the learners in this study claimed to be very tone aware and reported that they found listening and understanding Chinese more difficult than production. This is explored in relation to the pupils’ views about learning tones and pinyin and raises questions about the ways they address tones and pinyin learning in the context of their expressed aim of communicating and taking risks in speaking. The discussion raises issues about the possible effects of communicative teaching of languages in English schools. We ask whether an emphasis on communicative approaches may affect how learners address difficulties of the Chinese pronunciation system and the use of pinyin.